Improving immunization initiatives in the dynamics of a typhoid fever transmission model with environmental bacteria concentration - Tessema, Haileyesus; Zemenu, Yimer; Bizualem, Endlkachew; Teshome, Getachew (Frontiers in Applied Mathematics and Statistics, 2025)
Typhoid fever is a potentially fatal disease and endemic to most parts of the world. It is a serious worldwide health issue, especially in developing countries, and is typically spread via contaminated food, water, or drink. This work introduced an SIVR-B model to explore and predict the dynamics of typhoid disease in a community. The effective reproduction number (REff) of the model is calculated by manipulating the next-generation method. Then, after we computed the Typhoid fever-free equilibrium and the typhoid fever persistence equilibrium points, we demonstrated the global asymptotic stability of the equilibria. The bifurcation analysis demonstrated that the formulated typhoid model exhibits a forward bifurcation at REff = 1. Further, the sensitivity of parameters is performed using normalized forward sensitivity analysis and demonstrated using numerical simulation. The work demonstrated that higher typhoid vaccination rates have a pronounced effect on lowering disease transmission. From the results, we recommended policymakers and government stakeholders should enhance immunization efforts to effectively address the dynamics of typhoid fever transmission. In addition to improving vaccination efficacy, the research work recommends reducing poor drainage systems and improving water quality to reduce the infection number.